Breast-feeding, infant health and child survival in the Asia-Pacific context - United Nations (Asia-Pacific Population Journal, 1990)
An important distinguishing characteristic of mammals is that the female has mammae (breasts in human beings), the function of which is to secrete milk for the nourishment of newborn offspring. The availability of artificial means (bottles and formula milk) of feeding human infants has considerably reduced the dependency of infants on breast milk; however, the newborns of all other mammalian species remain exclusively dependent on mother’s milk for survival in early life. The milk produced by each species is particularly suited to the needs of newborns of that species. It is not surprising then that breast milk is the most suitable food for the human newborn.